Application of The Balanced Scorecard Method in Formulating Business Strategies to Enhance Sustainable Performance at PT Dedayu Opus Maxima - David Rusdianto; Maria Asumpta Evi Marlina (Dinasti Publisher, 2025)
The telecommunications industry in Indonesia has undergone rapid development in tandem with the proliferation of digital services and internet access. In this context, PT Dedayu Opus Maxima, as a provider of IT payment services, faces challenges in maintaining competitiveness amidst increasingly intense competition. The objective of this study is to formulate a pertinent and quantifiable business strategy that will enhance the company's sustainable performance, utilizing the Balanced Scorecard (BSC) approach. The BSC is a strategic management tool developed by Kaplan and Norton (1992) that integrates four main perspectives: financial, customer, internal business processes, and learning and growth. The present study employs a qualitative approach, utilizing interviews, observations, and company documentation to obtain data on BSC implementation at PT Dedayu Opus Maxima. The analysis is conducted with the objective of evaluating the effectiveness of the implemented business strategy and identifying areas that require improvement. The research findings indicate that the BSC evaluation shows suboptimal implementation, with low profitability, weak customer retention, and minimal reinforcement of learning and growth aspects. The business strategy of PT Dedayu Opus Maxima, formulated using a phased BSC approach, begins with human resource and system development, process optimization, and enhancement of customer loyalty and financial stability.